2010
DOI: 10.1007/978-3-642-15031-9_13
|View full text |Cite
|
Sign up to set email alerts
|

When Failure Analysis Meets Side-Channel Attacks

Abstract: Abstract. The purpose of failure analysis is to locate the source of a defect in order to characterize it, using different techniques (laser stimulation, light emission, electromagnetic emission...). Moreover, the aim of vulnerability analysis, and particularly side-channel analysis, is to observe and collect various leakages information of an integrated circuit (power consumption, electromagnetic emission ...) in order to extract sensitive data. Although these two activities appear to be distincted, they have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
(18 reference statements)
0
23
0
Order By: Relevance
“…To show that photonic side channel attacks are a real threat to cryptographic devices, other researchers suggested further research in this direction as well: "An interesting point for future research will be to re-do these experiments on [...] low-cost systems to validate the real benefit of them" [59]. We accomplished this task and showed that successful photonic side channel attacks do not require an awfully expensive measurement system.…”
Section: Symmetric Cryptographymentioning
confidence: 93%
See 2 more Smart Citations
“…To show that photonic side channel attacks are a real threat to cryptographic devices, other researchers suggested further research in this direction as well: "An interesting point for future research will be to re-do these experiments on [...] low-cost systems to validate the real benefit of them" [59]. We accomplished this task and showed that successful photonic side channel attacks do not require an awfully expensive measurement system.…”
Section: Symmetric Cryptographymentioning
confidence: 93%
“…In 2011, an integrated PICA system and laser stimulation techniques were used to attack a DES implementation on an FPGA [59]. The authors show that the optical side channel can be used for differential analysis.…”
Section: Photonic Emission For Attacking Cryptographymentioning
confidence: 99%
See 1 more Smart Citation
“…3.2.1 Electromagnetic Attacks These attacks deal with discerning the encoded plaintext of a power line message through the leakage of electromagnetic radiation [63,64]. These attacks use special probes placed at various locations along the unit or circuit in question.…”
Section: Decryption Attacksmentioning
confidence: 99%
“…These faults can be anything from unusual environmental conditions (increased heat, for example), the injection of a laser beam at the appropriate frequency [64], or the injection of data packets that collide with legitimate packets [71]. The work of Yuan and Liu [72][73][74] has shown the load redistribution attack.…”
Section: Fault Analysis Attackmentioning
confidence: 99%